(untitled) (Journal of the College of Basic Education, 2022)
Britain began to realize the power of Abdul Aziz bin Abdul Rahman bin Faisal Al Saud(1902-1953) in the Arabian Peninsula before the outbreak of World War I, so I sent him Captain Shakespeare ( ) ( Shakespeare, the political agent in Kuwait, who made several trips ( ) to the Arabian Peninsula, especially in 1913, which witnessed his meeting with Ibn Saud ( ) before his annexation Al-Ahsa, with the aim of bringing the latter closer to the princes of the Arabian Peninsula, especially after the outbreak of World War I in 1914 and beyond to support the British military effort in fighting the Ottoman Empire, and its allies from the Al-Rashid family, the princes of Hail, and based on reports ( ) Cox ( ) sent from Basra to the government of India And dated January 16, 1915, which indicated the existence of a tendency in many regions of the Arabian Peninsula to lean towards the Emir of Najd and Al-Ahsa (), with the presence of Sharif Al-Hijaz Al-Hussein bin Ali () in Makkah Al-Mukarramah ().